2019
DOI: 10.31989/ffhd.v9i9.621
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index and Load Responses of Indigenous Vegetable Sauces Among Healthy Young Female Adults

Abstract: Background: Diet-related chronic disease especially diabetes mellitus, cardiovascular disease (CVDs), obesity, hypertension and cancers is a major public health problem in Nigeria. The use of locally made foods has been advocated for in the management of diabetes mellitus in recent times.Methods: The recipe for the test food was developed and standardized. Proximate and dietary fibre analysis was carried out on the test food (okra, African spinach and lettuce sauces) and reference food (white bread). Thirty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The dough of T. triangulare was added and allowed to simmer for 5 min. It was brought down and served [11]. The local yam (Kponan) was prepared by peeling, slicing and was cooked until softened [6].…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…The dough of T. triangulare was added and allowed to simmer for 5 min. It was brought down and served [11]. The local yam (Kponan) was prepared by peeling, slicing and was cooked until softened [6].…”
Section: Methods Of Preparationmentioning
confidence: 99%
“…Fat slows down the rate of digestion in the intestine which gives a low glycemic index when compared with similar food with little or without fat [31]. However, Amadi et al [32] reported that these vegetable sauces (lettuce, African spinach and okra sauces) fed to normoglycemic subjects gave a low glycemic response irrespective of the fact that the fat content of the vegetable sauces was low. The implication of the study was that the recipe in the present study was designed in a way that fat contribution from palm oil was small which corresponds to the aim of diabetic management that is to reduce saturated fatty acids, trans-fatty acid and cholesterol intake so as to limit the risk of cardiovascular diseases.…”
Section: Proximate Dietary Fibre and Energy Composition Of Vegetablementioning
confidence: 99%